The Mentor-Mothers program in the Nigeria Department of Defense: policies, processes, and implementation - Josephine Moshe Ibu; Euphemia Mbali Mhlongo (BMC, 2022)
Abstract Background Nigeria has the second largest HIV epidemic in the world and is one of the countries with the highest rates of new pediatric infections in sub-Saharan Africa. The country faces several challenges in the provision of healthcare services and coverage of Prevention of Mother to child transmission of HIV. In the Nigeria's Department of Defense, prevention of vertically transmitted HIV infections has been given a boost by utilizing Mentor Mothers to facilitate antiretroviral compliance and retention in care. The aim of this study was to explore those processes and policies that guide the implementation of the Mentor Mothers program for PMTCT of HIV in the Department of Defense in Nigeria as no studies have examined this so far. Methods The descriptive, qualitative research approach was utilized. We conducted 7 key informants interviews with 7 purposively selected participants made up of 2 program Directors, 1 Doctor, 1 PMTCT focal Nurse, 1 PMTCT site coordinator, 1 Mentor Mother, and 1 patient from one each of the health facilities of the Army, Navy, Airforce and the Defence Headquarters Medical Centre. Open coding for major themes and sub-themes was done. Data were analyzed using thematic analysis. Results Findings revealed that the program in the Department of Defense had been modelled after the WHO and implementing partners' guidelines. Foundational Factors; Leadership; Skill acquisition; and Service Characteristics emerged as processes guiding the implementation of the Mentor-Mothers program in the DoD. These findings supported the Mentor Mother Model, which empowers mothers living with HIV - through education and employment - to promote access to essential PMTCT services and medical care to HIV positive pregnant women. Conclusion We concluded that no definitive policy establishes the Mentor Mothers program in the DoD. Working with Doctors, Nurses, local & collaborating partners, and communities in which these hospitals are located, the Mentor Mothers play a pivotal role in the formation, facilitation, and implementation of the MM model to effectively decrease HIV infections in children and reduce child and maternal mortality in women and families they interact with.